The basics of cloud computing understanding the fundamentals of cloud computing in theory and practice - Rountree, Derrick (Basics., 2014)
As part of the Syngress Basics series, The Basics of Cloud computing provides you with an overview of cloud computing technology and how you can implement cloud computing in your business. This book helps you understand what the cloud is and how to work with it.